Enhancing Wound Repair With Carica Papaya -Based Formulation: A Pretest-Posttest Control Group Trial - Mokh. Sujarwadi; Mukhammad Toha; Ida Zuhroidah; Rondhianto Rondhianto; Dimas Hadi Prayoga; Fatimah Zahra; Nadia Rohmatul Laili (PT.Mantaya Idea Batara, 2026)
Background: Natural products are increasingly favored in wound care due to concerns about antibiotic resistance and side effects of synthetic drugs. Carica papaya L., a tropical plant native to Central America and widely grown in Indonesia, contains bioactive compounds with properties essential for tissue repair. This study tests whether a topical Carica papaya formulation speeds up wound healing by measuring granulation and epithelialization. Methods: Using a quasi-experimental design. A total of 50 participants were divided into a control (standard wound care) and a treatment group (standard care + C. papaya extract). Analysis used the Paired T test. Result: Paired t-tests indicated no significant changes in the control group (p = 1.00). In contrast, the treatment group demonstrated statistically significant improvements in granulation (pre: 0.44 ± 0.51; post: 1.56 ± 0.51; t = -9.35, p < 0.001) and epithelialization (pre: 0.68 ± 0.47; post: 1.72 ± 0.46; t = -10.25, p < 0.001). Independent-samples t-tests confirmed significant differences between groups after the intervention (granulation: t = -9.35, p < 0.001; epithelialization: t = -10.25, p < 0.001). These results support the incorporation of C. papaya extract into evidence-based complementary wound management protocols. Conclusion: Carica papaya extract significantly enhances wound healing, promoting granulation and epithelialization. Thus, it may serve as an effective adjunctive therapy in clinical wound management.